Characterization of the binding of a glycosylated serine protease from Euphorbia cf. lactea latex to human fibrinogen. (11th May 2017) - Siritapetawee, Jaruwan; Talabnin, Chutima; Vanichtanankul, Jarunee; Songsiriritthigul, Chomphunuch; Thumanu, Kanjana; Chen, Chun‐Jung; Komanasin, Nantarat
Abstract: In this study, the binding of a glycosylated serine protease (EuP‐82) with human fibrinogen was investigated by isothermal titration calorimetry (ITC). ITC analysis indicated that the binding of EuP‐82 to fibrinogen in the conditions with or without the activator (Ca 2+ ) was an exothermic reaction (dominant negative enthalpy), which tended to be driven by hydrogen bonding and van der Waals interactions. In contrast, the binding of fibrinogen−EuP‐82 in the condition with the inhibitor (Zn 2+ ) was an unfavorable endothermic reaction. EuP‐82 could not inhibit the platelet activity in citrated whole blood via the ADP–receptor pathways (mainly, P2Y1 and P2Y12), but it could enhance the platelet aggregation. The ITC together with whole blood platelet aggregation suggested that EuP‐82 provided multiple fibrinogen‐binding sites that were not related to the arginine‐glycine‐aspartate (RGD) and the dodecapeptide sequences of fibrinogen. In addition, EuP‐82 had neither thrombin‐like activity nor anticoagulant activity. The SR‐FTIR spectra revealed that EuP‐82 was a glycoprotein. Deglycosylation of EuP‐82 did not affect its proteolytic activity. Moreover, EuP‐82 did not exhibit any toxicity to the living cells (NIH‐3T3). This study supports that EuP‐82 may be useful for wound‐healing material through stabilizing the clot via the platelet induction for the first process.